Identification of a Novel Class of Photolyases as Possible Ancestors of Their Family. (27th June 2021) - Xu, Lei; Chen, Simeng; Wen, Bin; Shi, Hao; Chi, Changbiao; Liu, Chenxi; Wang, Kangyu; Tao, Xianglin; Wang, Ming; Lv, Jun; Yan, Liang; Ling, Liefeng; et al.
Abstract: UV irradiation induces the formation of cyclobutane pyrimidine dimers (CPDs) and 6-4 photoproducts in DNA. These two types of lesions can be directly photorepaired by CPD photolyases and 6-4 photolyases, respectively. Recently, a new class of 6-4 photolyases named iron–sulfur bacterial cryptochromes and photolyases (FeS-BCPs) were found, which were considered as the ancestors of all photolyases and their homologs—cryptochromes. However, a controversy exists regarding 6-4 photoproducts only constituting ∼10–30% of the total UV-induced lesions that primordial organisms would hardly survive without a CPD repair enzyme. By extensive phylogenetic analyses, we identified a novel class of proteins, all from eubacteria. They have relatively high similarity to class I/III CPD photolyases, especially in the putative substrate-binding and FAD-binding regions. However, these proteins are shorter, and they lack the "N-terminal α/β domain" of normal photolyases. Therefore, we named them short photolyase-like. Nevertheless, similar to FeS-BCPs, some of short photolyase-likes also contain four conserved cysteines, which may also coordinate an iron–sulfur cluster as FeS-BCPs. A member from Rhodococcus fascians was cloned and expressed. It was demonstrated that the protein contains a FAD cofactor and an iron–sulfur cluster, and has CPD repair activity. It was speculated that this novel class of photolyases may be the real ancestors of the cryptochrome/photolyase family.